Pernikahan beda agama dalam perspektif Islam - Sufiandi, Mohammad Alvian (Maliki Interdisciplinary Journal, 2024)
Interfaith marriage is a complex social phenomenon, especially in Indonesia with its diversity of religions and beliefs. Islam has its own prerequisites for interfaith marriages, as explained in the Koran. Although there are differences of opinion among mufasir, the majority of ulama tend to prohibit marriage to individuals from the Ahlulkitab. Consideration of benefits and mafsadat is the basis for determining the legal status of interfaith marriages. The implementation of marriages that are not in accordance with religious law is regulated in Law Number 1 of 1974 Article 2, which emphasizes that marriages must be carried out in accordance with the procedures of each religion, with Islam prohibiting marriage to individuals of different religions. The Koran's discussion about interfaith marriages includes: marriage of Muslim men to polytheist women, Muslim women to polytheist men (QS al-Baqarah/2:221) marriage of Muslim men to Muslim women (QS al Māidah/5:5). The implementation of marriage must be in accordance with the legal procedures of each respective religion. Marriage is regulated in Law Number 1 of 1974 Article 2, which reads "Marriage is valid if it is carried out according to the laws of each religion and belief." So marriage must refer to the religious procedures of each adherent, in this case Islam does not allow marriage. with individuals of different religions.